Development of ternary solid dispersions with hydrophilic polymer and surface adsorbent for improving dissolution rate of carbamazepine - Tanja Vojinović; Djordje Medarević; Edina Vranić; Zorica Potpara; Marko Krstić; Jelena Djuriš; Svetlana Ibrić (Elsevier, 2018)
In this study solid dispersions of carbamazepine in the hydrophilic Kollidon® VA64 polymer, adsorbed onto Neusilin® UFL2 adsorption carrier have been employed to improve carbamazepine dissolution rate. In order to evaluate effects of changing in the proportions of all solid dispersion components on carbamazepine dissolution rate, D-optimal mixture experimental design was used in the formulation development. From all prepared solid dispersion formulations, significantly faster carbamazepine dissolution was observed compared to pure drug. Ternary solid dispersions containing carbamazepine, Kollidon® VA64 and Neusilin® UFL2 showed superior dissolution performances over binary ones, containing only carbamazepine and Neusilin® UFL2. Proportion of Kollidon® VA64 showed the most profound effect on the amount of carbamazepine dissolved after 10 and 30 min, whereby these parameters increase upon increasing in Kollidon® VA64 concentrations up to the middle values in the studied range of Kollidon® VA64 concentrations. Physicochemical characterization of the selected samples using differential scanning calorimetry, FT-IR spectroscopy, powder X-ray diffraction and polarizing light microscopy showed polymorphic transition of carbamazepine from more thermodynamically stable monoclinic form (form III) to less thermodynamically stable triclinic form (form I) in the case of ternary, but not of binary solid dispersion formulations. This polymorphic transition can be one of the factors responsible for improving of carbamazepine dissolution rate from studied solid dispersions. Ternary solid dispersions prepared with Kollidon® VA64 hydrophilic polymer and Neusilin® UFL2 adsorption carrier resulted in significantly improvement of carbamazepine dissolution rate, but formation of metastable polymorphic form of carbamazepine requires particular care to be taken in ensuring product long term stability. Keywords: Solid dispersions, D-optimal mixture experimental design, Surface adsorbent, Poorly soluble drugs, Polymorphism, Polymorphic conversion